Single Implant Restoration and Adhesive Bridge for Anterior teeth (A Case Report) - Machmud, Edy; Amiruddin, Maqhfirah (Hasanuddin University, 2019)
Objective : The aim of this case report restore healthy tooth function so that patients can chew food properly, so the method of implant placement is a good choice for patients with tooth loss. The adhesive bridge denture treatment aims to restore a missing tooth. The indication of adhesive bridge denture treatment is a mild contact of occlusion, young patients and good oral hygiene.Methods : On first visit doing filling status and patient signed an informed consent and making study casts, then proceed with making a surgical templete. After that, a ct-scan was performed to determine the size of the implant that matches the size of the available bone. The second visit, carried out the edentulous 36 implantation process using implants measuring 3.7mm in diameter and 12 mm in length with the EZ Dent-I IDI brand. Third visit, tooth color selection wih shade guide, and preparation of the palatal part of abutment teeth 12 and 21 was made for bridge adhesive in edentulous teeth 11. Two months later, double impression was performed for the manufacture of supra structural teeth .Results : The advantage of dental implants is that they closely resemble natural teeth because they are embedded in the tissue so they can support aesthetics, protection of adjacent teeth and the development of self-confidence. Bone density obtained from Ct-Scan radiographic greatly determines this treatment choice, the higher the bone density, the better the prognosis produced.Conclusion : The use of dentures with implant support for posterior mandibular teeth and adhesive bridge dentures for maxillary anterior teeth provides satisfaction for patients because it can overcome aesthetic problems and improve good phonetic and masticatory functions.Keywords: Adhesif Bridge, Bone Density, Ct-Scan, Dental Implant.